Analisis Bauran Pemasaran dalam Upaya Meningkatkan Partisipasi Anggota di Koperasi Karyawan Sejahtera Universitas PGRI, Yogyakarta - Kalifatullah Ermaya, Sir; Nur Laela Ermaya, Husnah; Mulyana, Iwan (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The existence of cooperatives as the center of economic activity for most Indonesians has begun to be displaced by competitors such as more modern shops and mini markets. Therefore, improving the quality of service and member participation in the cooperative is important in improving its business. Researchers conducted research using qualitative methods and used descriptive statistics to determine the marketing mix and member participation in the Sejahtera Employees Cooperative, PGRI University, Yogyakarta. The sampling technique used was simple random sampling with a total of 30 respondents. There are twenty-six indicators which fall into ten dimensions and two variables. In conveying messages about their products to consumers, all dimensions of the marketing mix variables and member participation in the Sejahtera Employees Cooperative, PGRI University, Yogyakarta fall into the very high category. The dimension with the best score is the place with a score of 4.98. Meanwhile, the dimension with the lowest score is processed with a score of 4.57. This shows that the Prosperous Employee Cooperative, PGRI University, Yogyakarta has implemented the 7P marketing mix and member participation well.